Perception of the self-image and body satisfaction in teenagers: perspective of nursing integral care - Cecília Nogueira Valença; Raimunda Medeiros Germano (Rev Rene)
This study aims to reflect on the self-perception of body image in the context of adolescence and the insertion of nursing in an integral perspective on this issue. This review of literature confirmed that the teenagers live a transitional phase, in which they present a series of transformations of biological, social, psychical and emotional dimensions. They also confirmed that such facts will reflect in adult life. This process of building their identity is part of their body perception, involving satisfaction with their self-image and dissatisfaction with their apparently physical imperfections. Then, it is important that the nurse acts also in the satisfaction of self-body image of adolescents, while acting in other aspects of the person’s health which has, in fact, his integral approach.